Analysis of the Values of Bhinneka Tunggal Ika in Character Formation of Class X - Feby A Sigalingging; Kondios Meidarlin Pasaribu; Hotmaida Simanjuntak; Monalisa Marta Siahaan; Lukman Pardede (STABN RADEN WIJAYA WONOGIRI, 2021)
This study aims to analyze how the values of Bhinneka Tunggal Ika are applied in the character building process of class X MPLB 1 students at SMK Negeri 1 Medan. Values such as tolerance towards cultural, religious, and ethnic differences are the main focus in building the character of students who are moral and have a national perspective. Through a descriptive qualitative approach, data were collected through observation, interviews with teachers and students.The results of the study show that the values of Bhinneka Tunggal Ika have been integrated into learning activities and daily life at school, both directly through lesson materials and through students' social interactions. The application of these values helps shape students' characters to be more tolerant, open to differences, and able to work together in a multicultural environment. In addition, the existence of school programs that support diversity also strengthens students' understanding of the diversity that exists